The Impact of Management Practices on SME Performance - John Forth; Alex Bryson (Institute of Labor Economics (IZA), 2018)
We examine the impact of management practices on firm performance among SMEs in Britain over the period 2011-2014, using a unique dataset which links survey data on management practices with firm performance data from the UK's official business register. We find that SMEs are less likely to use formal management practices than larger firms, but that such practices have demonstrable benefits for those who use them, helping firms to grow and increasing their productivity. The returns are most apparent for those SMEs that invest in human resource management practices, such as training and performance-related pay, and those that set formal performance targets.
Keywords: L25; L26; M12; M52; M53; 330; SMEs; small and medium-sized enterprises; employment growth; high-growth firms; productivity; workplace closure; management practices; HRM; recession